Tinjauan Implementasi Fatwa DSN NO.25/DSN-MUI/III/2002 Pada Pelaksanaan Penjualan Barang Gadai Yang Tidak Ditebus Di Bank JATIM Syariah - Khurin Fijria Nuzula; Irham Zaki (Universitas Airlangga, 2016)
The purpose of this research is to assess the compliance of the selling procedures for unredeemed pawn goods (Marhun) in accordance to the National Sharia Council’s Fatwa No:25/DSN-MUI/III/2002 in Bank Jatim Syariah. The selling of unredeemed pawn goods (marhun) is analyzed from 4 aspects : (1) Maturity, (2) the execution of sale, (3) the result of the sale and (4) the excess or deficit from the result of the sale. This research adopts a qualitative approach with a case study methodology. The result of this research suggests that there is incompliance to the National Sharia Council’s Fatwa No:25/DSN-MUI/III/2002 in the act of selling unredeemed pawn goods (marhun) by Bank Jatim Syariah, however this incompliance does not indicate any breach to the sharia rulings on sales and purchase.